PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN PADA KANTOR SATPOL PP DAN WH ACEH - Cahya, Nilam (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2020)
The Employee Attendance Information System is one of the data processing activities at the Satpol PP and WH Aceh Offices, to get information about attendance to be more targeted and easy to obtain. In writing this Final Assignment (TA), the author only discusses the problem of attendance and data management mechanisms at the Satpol PP and WH Aceh Offices and designs an Employee Attendance Information System using Visual BASIC.NET. The purpose of writing is to understand the problem of attendance and data management at the Satpol Office. PP and WH Aceh as well as making auxiliary applications about Employee Attendance Information Systems using Visual BASIC.NET, the collection of data needed in writing this report was obtained by two methods, namely literature studies related to literature, library books and other scientific works, studies field by conducting interviews and direct observation of objects related to this Final Project (TA). Employee Attendance Information System is carried out by one of the administrative staff in the field of administration to record and input attendance data. From the results of the study, it can be concluded that the Employee Attendance Information System at the Satpol PP and WH Aceh Offices has followed procedures and uses computers with the Visual BASIC.NET 2010 language program and Microsoft Access as the database.